IMPLEMENTATION OF SHARIA MANAGEMENT FUNCTION IN THE MANAGEMENT OF TABEK MANDI SIKABU BALINGKA, AGAM REGENCY - Eli Febriani; Habibatur Ridha, Rayzul Hawari (Adisam Publisher, 2024)
This study aims to determine the application of sharia management functions in managing business in Tabek Mandi Sikabu and to find out the supporting factors and become obstacles to the implementation of sharia management functions in managing business in Tabek Mandi Sikabu The type of research is descriptive qualitative, using methods, observational interviews and documentation with the manager of Tabek Mandi Sikabu Balingka Agam Regency to obtain accurate data, real and precise. From the results of this study, the application of sharia management functions in managing business in Tabek Mandi Sikabu was carried out. The planning process is carried out by establishing work programs for the long, medium and short term. The organizing process is carried out by distributing jobdesks, employee recruitment, and training for employees. Then the actuating process is carried out by guiding, motivating to equalize the expected goals. Finally, the controlling process is carried out by supervising oneself by receiving input from others, checking employee performance in the field and supervised by the tourism office. For inhibiting and supporting factors for the implementation of sharia management functions in Tabek Mandi Sikabu, namely the absence of a written vision and mission, the absence of a complete organizational structure, the absence of swimming pool facilities in accordance with sharia. For supporting factors, there is also support from visitors for the provision of sharia bathing facilities.